Lineage-biased hematopoietic stem cells are regulated by distinct niches - Pinho, Sandra (Dev Cell, 2018)
The spatial localization of hematopoietic stem cells (HSCs) in the bone marrow (BM) remains controversial with studies suggesting that they are maintained in homogenously distributed niches while others have suggested the contributions of distinct niche structures. Subsets of quiescent HSCs have been reported to associate with megakaryocytes (MK) or arterioles in the BM. However, these HSC subsets have not been prospectively defined. Here, we show that platelet and myeloid-biased HSCs, marked by von Willebrand factor (vWF) expression, are highly enriched in MK niches. Depletion of MK selectively expands vWF(+) HSCs whereas the depletion of NG2(+) arteriolar niche cells selectively depletes vWF(−) lymphoid-biased HSCs. In addition, MK depletion compromises vWF(+) HSC function by reducing their long-term self-renewal capacity, and eliminating their lineage bias after transplantation. These studies demonstrate the existence of two spatially and functionally separate bone marrow niches for HSC subsets with distinct developmental potential.